Corporate responsibility - Blowfield, Mick (Oxford University Press, 2011)
"Corporate Responsibility provides an original framework for examining the multiple dimensions to corporate responsibility, and identifies the main trends, arguments, and themes that underpin the subject. Packed with pedagogical features and including a wealth of mini case studies such as General Electric, Traidcraft Plc, and UN Principles for Responsible Investment, this text is an invaluable resource for students taking a module in corporate responsibility."--BOOK JACKET.